Antibacterial Activity of Bitter Drugs from Lingga Malay Ethnic in Riau Archipelago Against Bacterial Causing Skin and Diarrhea Diseases - Rahma Dhani; Rodesia Mustika Roza; Fitmawati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Infection is the major threat to humanity caused by infectious agents. The most common infectious agent of human is the cause of skin and diarrhea diseases. Melayu Lingga people uses alternative medicine called obat pahit potion to treat skin and diarrhea diseases and mixes by Praktisi Obat Tradisional (POT). The purpose of this research was to determine antibacterial activity of the methanol extract from obat pahit potion against bacteria that cause skin diseases (Staphylococcus aureus ATCC 12600, Staphylococcus epidermidis ATCC 12228, Pseudomonas aeruginosa ATCC 10145) and diarrhea (Escherichia coli ATCC 11775, Salmonella typhi ATCC 14028, Shigella flexneri ATCC 12022) by using disc diffusion method with variation of extract concentration (0.75 gr/ml, 0.5 gr/ml, and 0.25 gr/ml). Antibacterial activity was determined by measuring the inhibitory zone formed around the disc. Based on the result of antibacterial activity test, the largest inhibitory zone was found in S.aureus ATCC 12600, S.epidermidis ATCC 12228 and P.aeruginosa ATCC 10145 shown in POT Musai at 0.25 mg/ml concentrations with value 6,61 mm; 6,10 mm; and 10,11 mm. Meanwhile, antibacterial activity against E.coli ATCC 11775 shown in TMP Musai at 0.5 gr/ml concentration with value 4,47 mm. Antibacterial activity against S.typhi ATCC 14028 and S.flexneri ATCC 12022 shown in TMP Musai at 0.25 gr/ml concentration with value 8,20 mm and 11,73 mm.